Manufacturing process of high performance nanomaterial ceramic thin film devices

By using 10-60nm alumina particles to prepare alumina gels and fused with the target to prepare ceramic films. Combined with sintering and heat treatment technology, the problems of substrate selection and stability of nanomaterial ceramic film devices are solved, significantly improving the performance and stability of the device.

CN116621587BActive Publication Date: 2025-05-02KUNMING UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310640068.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-01
Publication Date
2025-05-02
Estimated Expiration
2043-06-01

AI Technical Summary

Technical Problem

When preparing nanomaterial ceramic films, improper substrate selection and high instability are prone to impurities and cracks, which affects the stability and reliability of the device and cannot be fully guaranteed.

Method used

Alumina gel is prepared by reacting alumina particles with a particle size of 10-60 nm by reacting alumina with solution, and then fusing it with the target to prepare a ceramic film, and the crystallinity and grain size of the film are improved by sintering and heat treatment.

Benefits of technology

By improving the density and uniformity of the alumina substrate, the quality and performance of the ceramic film are improved, and its physical properties and chemical stability are improved, and the stability and reliability of the device are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116621587B_ABST
    Figure CN116621587B_ABST
Patent Text Reader

Abstract

The present invention discloses a manufacturing process of a high-performance nanomaterial ceramic film device, which belongs to the technical field of nano-ceramic materials, and includes the following steps: S1, preparing nanomaterials: preparing alumina gel by reacting alumina with a solution; S2, preparing ceramic film: fusing alumina gel and a target material to prepare a ceramic film; S3, sintering treatment: sintering the ceramic film; S4, processing: surface treating and testing the sintered ceramic film, and finally making a specified article. In one or more embodiments of the present invention, alumina particles with a particle size of 10-60nm are selected. In the present invention, by using alumina particles with a higher specific surface area and a smaller particle size to make a substrate, the density and uniformity of the base can be improved, thereby improving the quality and performance of the ceramic film. At the same time, mixing alumina with ethanol can ensure the purity and stability of the base, and avoid the interference of impurities in the preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano ceramic materials, in particular to a manufacturing process of high-performance nano material ceramic thin film devices. Background Art

[0002] Nanomaterial ceramic film is a film made of nano-scale ceramic material, and its thickness is usually between a few nanometers and tens of nanometers. This film has excellent physical and chemical properties such as high hardness, high wear resistance, high corrosion resistance, and high temperature stability. Therefore, it is widely used in electronics, optoelectronics, energy, biomedicine and other fields.

[0003] Nanomaterial ceramic thin film devices are devices made of ceramic thin films prepared using nanomaterials; common nanomaterial ceramic thin film devices include sensors, capacitors, resistors, piezoelectric devices, thermistors, gas sensitive resistors, etc.

[0004] When preparing nanomaterial ceramic films, due to different choices of substrates, the instability coefficient leads to the easy appearance of impurities and cracks, which affects the stability and reliability of subsequent device manufacturing, and thus the performance of the device cannot be fully guaranteed. Therefore, a manufacturing process for high-performance nanomaterial ceramic film devices is proposed. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, one object of the present invention is to provide a manufacturing process for a high-performance nanomaterial ceramic thin film device.

[0006] To achieve the above object, the present invention provides the following technical solution: A manufacturing process of a high-performance nanomaterial ceramic thin film device comprises the following steps:

[0007] S1. Preparation of nanomaterials: preparing alumina gel by reacting alumina with a solution;

[0008] S2, preparing a ceramic film: fusing the alumina gel and the target material to prepare a ceramic film;

[0009] S3, sintering treatment: sintering the ceramic film;

[0010] S4. Processing: The sintered ceramic film is surface treated and tested, and finally made into a designated object.

[0011] In one or more embodiments of the present invention, in step S1, alumina particles with a particle size of 10-60 nm and ethanol with a purity of 99.5% are selected to prepare a 3 cm alumina substrate, and the concentration of the alumina nanoparticles is 0.18 g / ml. The volume of ethanol required to prepare the ceramic film is 10 ml, and the volume of acetic acid is 5 ml.

[0012] In one or more embodiments of the present invention, in step S1, the specific steps are:

[0013] Pour 10 ml of ethanol into a 50 ml beaker, add 0.1 g of alumina nanoparticles, treat with ultrasound for 30-45 min, then add 5 ml of acetic acid to evenly disperse it to obtain a transparent sol, place an alumina substrate in the sol and soak it for 10 min to allow the alumina nanoparticles in the sol to deposit on the surface of the substrate to form a gel, and place the gel in a drying oven to dry to obtain an alumina gel.

[0014] In one or more embodiments of the present invention, in step S2, the alumina gel is taken out and placed in a furnace for calcination for 2-3.5 hours to obtain alumina nanopowder.

[0015] In one or more embodiments of the present invention, in step S2, an aluminum silicide target is placed in a vapor deposition device, and the material on the surface of the target is deposited on the aluminum oxide nanopowder through a high temperature and high pressure vapor phase reaction to form a thin film. The thin film is placed in an oven and dried at 80°C for 30-50 minutes. The above steps are repeated 2-5 times until the film reaches 3 cm.

[0016] In one or more embodiments of the present invention, in step S2, the prepared film is placed in an oven and steamed and baked at 400-600° C. for 2-4 hours to crystallize it into a ceramic film.

[0017] In one or more embodiments of the present invention, in step S3, the ceramic film is placed in a furnace, the temperature in the furnace is set to 1300-1800°C, the firing time is 3-5h, the sintering pressure is 10-20MPa, the ceramic film melts and forms a crystal structure, and after cooling, the sintered ceramic film is taken out.

[0018] In one or more embodiments of the present invention, in step S4, an atomic force microscope (AFM) is used to observe and analyze the surface flatness, particle distribution and roughness of the ceramic film, an X-ray diffractometer (XRD) is used to analyze the crystal structure, grain size and grain boundaries of the ceramic film, an electrical testing system is used to test the resistivity, dielectric constant, permittivity and conductivity of the ceramic film, and a universal material testing machine is used to test the hardness, elastic modulus and fracture toughness of the ceramic film.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] In the present invention, by using alumina particles with a high specific surface area and a small particle size to make the substrate, the density and uniformity of the base can be improved, thereby improving the quality and performance of the ceramic film. At the same time, the mixture of alumina and ethanol can ensure the purity and stability of the base and avoid the interference of impurities in the preparation process.

[0021] In the present invention, the crystallization of the film and the growth of grains are promoted by heat treatment, thereby increasing the crystallinity and grain size of the film, and improving the physical properties and chemical stability of the film; in addition, the heat treatment can also remove organic matter and moisture in the film, increase the density and hardness of the film, and after sintering, the physical properties and chemical stability of the ceramic film will be significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a schematic diagram of the process of the high-performance nanomaterial ceramic thin film device of the present invention. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Embodiment 1:

[0025] The present invention provides a technical solution:

[0026] The manufacturing process of high-performance nanomaterial ceramic thin film devices includes the following steps:

[0027] S1. Preparation of nanomaterials: preparing alumina gel by reacting alumina with a solution;

[0028] S2, preparing a ceramic film: fusing the alumina gel and the target material to prepare a ceramic film;

[0029] S3, sintering treatment: sintering the ceramic film;

[0030] S4. Processing: The sintered ceramic film is surface treated and tested, and finally made into a designated object.

[0031] Specifically, in step S1, aluminum oxide particles with a particle size of 10-60 nm and ethanol with a purity of 99.5% are selected to prepare a 3 cm aluminum oxide substrate, and the concentration of aluminum oxide nanoparticles is 0.18 g / ml. The volume of ethanol required to prepare the ceramic film is 10 ml, and the volume of acetic acid is 5 ml.

[0032] Among them, alumina particles with a particle size of 10-60nm are selected because such particles have a higher specific surface area and a smaller particle size, which can improve the density and uniformity of the alumina substrate, thereby improving the quality and performance of the ceramic film; at the same time, ethanol with a purity of 99.5% can ensure the purity and stability of the base and avoid the interference of impurities in the preparation process; the concentration of alumina nanoparticles is 0.18g / ml to ensure the dispersion and uniformity of the particles, thereby improving the quality of the base; the volume of ethanol required for the preparation of ceramic films is 10ml, and the volume of acetic acid is 5ml to ensure the concentration and stability of the solution, thereby improving the quality and performance of the ceramic film.

[0033] Specifically, in step S1, the specific steps are:

[0034] Pour 10 ml of ethanol into a 50 ml beaker, add 0.1 g of alumina nanoparticles, treat with ultrasound for 30-45 min, then add 5 ml of acetic acid to evenly disperse it to obtain a transparent sol, place an alumina substrate in the sol and soak it for 10 min to allow the alumina nanoparticles in the sol to deposit on the surface of the substrate to form a gel, and place the gel in a drying oven to dry to obtain an alumina gel.

[0035] Among them, acetic acid is added to adjust the pH value of the solution to make it suitable for the dispersion of aluminum oxide nanoparticles; the aluminum oxide substrate is immersed in the sol to allow the aluminum oxide nanoparticles in the sol to deposit on the surface of the substrate to form a gel; finally, the gel is placed in a drying oven for drying to remove moisture and make the aluminum oxide gel denser and harder.

[0036] Specifically, in step S2, the alumina gel is taken out and placed in a furnace for calcination for 2-3.5 hours to obtain alumina nanopowder.

[0037] Among them, after the alumina gel is taken out, it needs to be placed in an oven for calcination; the purpose of calcination is to remove moisture and organic matter in the gel and convert it into alumina nanopowder; the furnace temperature should be between 500-800°C, and the calcination time should be 2-3.5 hours, which can ensure that the moisture and organic matter in the gel are completely removed, while avoiding excessive calcination that causes the powder particles to be too large; the alumina nanopowder obtained after calcination has higher purity and smaller particle size.

[0038] Specifically, in step S2, the aluminum silicide target is placed in a vapor deposition device, and the material on the surface of the target is deposited on the aluminum oxide nanopowder through a high temperature and high pressure vapor phase reaction to form a thin film. The thin film is placed in an oven and dried at 80°C for 30-50 minutes. The above steps are repeated 2-5 times until the film reaches 3 cm.

[0039] The preparation steps of the aluminum silicide target are as follows:

[0040] Pick up alumina powder and silicon powder. The purity of alumina powder is required to be higher than 99.99%, and the purity of silicon powder is required to be higher than 99.999%. Mix the high-purity alumina powder and silicon powder in a ratio of 1:15 to obtain a mixed powder. Put the mixed powder into a pressing mold for pressing. The pressing pressure is between 100MPa and the pressing time is between 8min. Put the pressed target material into a sintering furnace for sintering treatment. The sintering temperature is between 1750℃ and the sintering time is between 2 hours. Perform surface treatment on the sintered target material, usually using mechanical polishing to make its surface flat and smooth.

[0041] Specifically, in step S2, the prepared film is placed in an oven and steamed and baked at 400-600° C. for 2-4 hours to crystallize it into a ceramic film.

[0042] Among them, heat treatment is used to promote the crystallization of the film and the growth of grains, thereby increasing the crystallinity and grain size of the film, and improving the physical properties and chemical stability of the film; in addition, heat treatment can also remove organic matter and moisture in the film, and improve the density and hardness of the film.

[0043] Specifically, in step S3, the ceramic film is placed in a furnace, the temperature in the furnace is set to 1300-1800°C, the firing time is 3-5h, the sintering pressure is 10-20MPa, the ceramic film melts and forms a crystal structure, and after cooling, the sintered ceramic film is taken out.

[0044] Among them, the ceramic film is placed in a furnace for sintering in order to form a denser crystal structure and improve its physical properties and chemical stability. At high temperatures, the grains in the ceramic film will gradually grow and combine to form larger crystals, thereby increasing its grain size and the quality of grain boundaries. At the same time, the sintering pressure at high temperatures also helps to eliminate pores and defects in the ceramic film, further improving its density and strength. After sintering, the physical properties and chemical stability of the ceramic film will be significantly improved.

[0045] As can be seen from the above, the temperature in the furnace is set to 1300-1800℃, because the melting point of ceramic materials is usually high, and a higher temperature is required to melt them; the firing time is 3-5 hours to ensure that the ceramic film is fully sintered to form a dense structure; the sintering pressure is 10-20MPa, so that the ceramic film can maintain a certain shape and density during the sintering process to avoid defects such as cracks or holes; the sintered ceramic film needs to be cooled and then taken out for subsequent testing and application.

[0046] Specifically, in step S4, an atomic force microscope (AFM) is used to observe and analyze the surface flatness, particle distribution and roughness of the ceramic film, an X-ray diffractometer (XRD) is used to analyze the crystal structure, grain size and grain boundaries of the ceramic film, an electrical testing system is used to test the resistivity, dielectric constant, permittivity and conductivity of the ceramic film, and a universal material testing machine is used to test the hardness, elastic modulus and fracture toughness of the ceramic film.

[0047] Among them, surface flatness: the surface should be flat and smooth, without obvious protrusions or depressions; particle distribution: the particle distribution should be uniform, without aggregation; roughness: the degree of unevenness on the surface of the ceramic film, expressed by the Ra value, which needs to be below 0.1μm.

[0048] The crystal structure of the ceramic film should be complete, defect-free, and have good crystal orientation; the grain size should be small enough to improve the mechanical properties and surface flatness of the film; the grain boundaries should be as few as possible and be clear and continuous to improve the chemical stability and electrical properties of the film.

[0049] Resistivity: The resistivity of the testing ceramic film should be high so that it can be used to make high-resistance resistors and sensors, between 10^6-10^14Ω·cm; Dielectric constant: The dielectric constant of the ceramic film should be between 2-10; Permittivity: The permittivity of the ceramic film should be between 10^-12-10^-6F / cm^2; Conductivity: The conductivity of the ceramic film should be between 10^-12-10^2S / cm.

[0050] Embodiment 2:

[0051] Prepare aluminum oxide solution: Pour 99.5% pure ethanol into a 50 ml beaker, add aluminum oxide particles of different particle sizes (10-20 nm, 30-40 nm, 50-60 nm), treat with ultrasound for 30-45 minutes, and then add 5 ml of acetic acid to evenly disperse it to obtain a transparent sol.

[0052] Preparation of alumina substrate: placing the alumina substrate in the sol and soaking it for 10 minutes to allow the alumina nanoparticles in the sol to be deposited on the surface of the substrate to form a gel, and placing the gel in a drying oven to dry it to obtain an alumina gel.

[0053] Preparation of ceramic film: Take out the alumina gel and put it into the oven for calcination for 2-3.5 hours to obtain alumina nanopowder. Place the aluminum silicide target in the vapor deposition equipment, and deposit the material on the target surface on the alumina nanopowder through high temperature and high pressure vapor phase reaction to form a film. Place the film in an oven and dry it at 80°C for 30 minutes. Repeat the above steps 4 times until the film reaches 3 cm.

[0054] Sintering treatment: Place the prepared film in an oven and bake it at 600°C for 3 hours to crystallize it into a ceramic film.

[0055] Processing: The sintered ceramic film is surface treated and tested, and finally made into a specified object.

[0056] In Example 1 and Example 2, the thickness and surface quality of the ceramic films prepared using alumina particles of different particle sizes are shown in the following table:

[0057] Alumina particle size Ceramic film thickness (mm) surface quality 10-20nm2.8 good 30-40nm2.9 good 50-60nm3.1 generally

[0058] Experimental results: The surface quality of ceramic films prepared using 10-20nm and 30-40nm alumina particles is good, while the surface quality of ceramic films prepared using 50-60nm alumina particles is average. Therefore, it is better to use alumina particles with smaller particle sizes to prepare ceramic films.

[0059] Parts not involved in the present invention are the same as the prior art or can be implemented by the prior art. Although the embodiments of the present invention have been shown and described, it is understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. The manufacturing process of high-performance nanomaterial ceramic thin film devices is characterized by: The following steps are involved: S1. Preparation of nanomaterials: preparing alumina gel by reacting alumina with a solution; The specific steps are as follows: pour 10 ml of ethanol into a beaker with a capacity of 50 ml, add 0.1 g of aluminum oxide nanoparticles, treat with ultrasound for 30-45 min, then add 5 ml of acetic acid to make it evenly dispersed to obtain a transparent sol, put an aluminum oxide substrate into the sol and soak it for 10 min to make the aluminum oxide nanoparticles in the sol deposit on the surface of the substrate to form a gel, and place the gel in a drying oven to dry to obtain an aluminum oxide gel; S2, preparing a ceramic film: fusing the alumina gel and the target material to prepare a ceramic film; Specifically, the alumina gel is taken out and placed in a furnace for calcination for 2-3.5 hours to obtain alumina nanopowder; Place the aluminum silicide target in a vapor deposition device, and deposit the material on the target surface on the aluminum oxide nanopowder through a high temperature and high pressure vapor phase reaction to form a thin film. Place the thin film in an oven and dry it at 80°C for 30-50 minutes. Repeat the above steps 2-5 times until the film reaches 3 cm. Put the prepared film into an oven and steam and bake it at 400-600°C for 2-4 hours to crystallize it into a ceramic film; S3, sintering treatment: sintering the ceramic film; Specifically, the ceramic film is placed in a furnace, the temperature in the furnace is set to 1300-1800°C, the firing time is 3-5h, the sintering pressure is 10-20MPa, the ceramic film is melted and forms a crystal structure, and after cooling, the sintered ceramic film is taken out; S4. Processing: The sintered ceramic film is surface treated and tested, and finally made into a designated object.

2. The manufacturing process of the high-performance nanomaterial ceramic thin film device according to claim 1 is characterized in that: In step S1, aluminum oxide particles with a particle size of 10-60 nm and ethanol with a purity of 99.5% are selected to prepare a 3 cm aluminum oxide substrate, and the concentration of aluminum oxide nanoparticles is 0.18 g / ml. The volume of ethanol required to prepare the ceramic film is 10 ml, and the volume of acetic acid is 5 ml.

3. The manufacturing process of the high-performance nanomaterial ceramic thin film device according to claim 1 is characterized in that: In step S4, an atomic force microscope (AFM) is used to observe and analyze the surface flatness, particle distribution and roughness of the ceramic film, an X-ray diffractometer (XRD) is used to analyze the crystal structure, grain size and grain boundaries of the ceramic film, an electrical testing system is used to test the resistivity, dielectric constant, permittivity and conductivity of the ceramic film, and a universal material testing machine is used to test the hardness, elastic modulus and fracture toughness of the ceramic film.

Citation Information

Patent Citations

  • Surface pre-oxidized AlCrVTiSiON nano gradient coating and preparation method thereof

    CN118086830A